Sensitivity of Papilledema as a Sign of Increased Intracranial Pressure - Krahulik, David; Hrabalek, Lumir; Blazek, Filip; Halaj, Matej; Slachta, Marek; Klaskova, Eva; Maresova, Klara (Children, 2023)
Our study evaluates the sensitivity of papilledema as a sign of high intracranial pressure in children. Patients younger than 18 years old, diagnosed with increased ICP, and who had received dilated fundus examination between 2019 and 2021 were retrospectively reviewed. Factors including the patient's age, sex, aetiology, duration of signs or symptoms, intracranial pressure (ICP), and presence of papilledema were evaluated. We included 39 patients in this study, whose mean age was 6.7 years. The 31 patients without papilledema had a mean age of 5.7 years, and 8 patients (20%) with papilledema had a mean age of 10.4 (p < 0.037). The mean duration of signs or symptoms was nine weeks in patients without papilledema and seven weeks in those with papilledema (p = 0.410). The leading causes of increased ICP with papilledema were supratentorial tumor (12.5%), infratentorial tumor (33.3%), and hydrocephalus (20%) (p = 0.479). Papilledema was statistically significantly more common in older patients. We found no statistical significance between sex, diagnosis, and symptoms. The relatively low incidence of papilledema (20%) in our study shows that papilledema's absence does not ensure the absence of increased ICP, especially in younger patients.